2012
DOI: 10.1590/s0102-09352012000400041
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the coding region of Slc11a1 (Nramp1) gene associated to natural resistance against bovine brucellosis

Abstract: Communication [Comunicação] Polymorphisms of the coding region of Slc11a1 (Nramp1) gene associated to natural resistance against bovine brucellosis[Polimorfismos na região codificadora do gene Slc11a1 (Nramp1) associados à resistência natural contra brucelose bovina]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…It was observed that naturally infected susceptible cows were often homozygous for the polymorphism, exhibiting the CC genotype in SPN4, and AA in SPN5. These results can support genetic selection of resistant animals (Paixão, Martinez & Santos 2012).…”
Section: Brucellosissupporting
confidence: 55%
See 1 more Smart Citation
“…It was observed that naturally infected susceptible cows were often homozygous for the polymorphism, exhibiting the CC genotype in SPN4, and AA in SPN5. These results can support genetic selection of resistant animals (Paixão, Martinez & Santos 2012).…”
Section: Brucellosissupporting
confidence: 55%
“…The gene encodes a transmembrane transporter located in the phagolysosome, which contributes to the bactericidal activity of macrophages. In cattle, natural resistance to B. abortus is associated with polymorphisms in the microsatellite 3'untranslated region (3'UTR) of the Slc11a1 gene, but the association between this polymorphism and natural infection remains controversial (Paixão, Martinez & Santos 2012). Martínez et al (2008) studied three polymorphisms in the gene Slc11a1 (SNP4, 5, and 6).…”
Section: Brucellosismentioning
confidence: 99%
“…Importantly, some evidence suggests that peripheral blood leukocytes from Zebu may respond differently than cells from European breeds when stimulated (Turni et al, 2002). Furthermore, clear differences have been observed in the frequency of alleles of Nramp1, a gene that has been linked to natural resistance to intracellular pathogens (Paixão et al, 2006(Paixão et al, , 2012. Susceptibility to infection is partially determined by genetic or physical characteristics (O'Kelly and Spiers, 1976), but it is also related to the profile and pattern of immune response of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al (2011) reported no association of g. 221K and g.642R with Brucellosis resistance trait in cattle. However, many previous studies reported that bovine Tuberculosis resistance can be associated by many SNP's of NRAMP1 gene at 3'UTR (Kadarmideen et al, 2011); exon 4, intron 4 (Cheng et al, 2015); exon 9, exon 11 (Baqir et al, 2016), intron 9, intron 12 (Liu et al, 2016), exon 10 and exon 11 (Paixao et al, 2012) regions. Nonetheless, Joo et al (2003) reported monomorphism in the exon 5 of NRAMP gene in healthy and infected Mastitis cows.…”
Section: Discussionmentioning
confidence: 99%